Calcinosis and myocarditis in systemic lupus erythematosus patient - Dewi, Sumartini; Wachjudi, Rachmat Gunadi (Indonesian Rheumatology Association, 2010)
Systemic lupus erythematosus (SLE) patients have multi-organ involvement related to their chronic inflammatory, autoimmune disease. Calcinosis can be clinical manifestations of SLE. Tissue calcinosis is reported in approximately 17% patients and myocarditis in 20-55% patients. Thus, both manifestations are not unusual in SLE. Tachypnea, tachycardia, pericardial effusion, and wheezing are often present and can be misleading in SLE patient.1,2 Calcinosis is less common in SLE, sometimesit is found as an incidental radiological finding. Calcification in SLE maybe periarticular, within joints or muscles, or in the subcutis (calcinosis universalis).1 Calcinosis is classified into four subsets: dystrophic, metastatic, idiopathic, or calciphylaxis/iatrogenic. When calcinosis cutis is isolated to a small area in extremities and joints, it is called calcinosis circumscripta; whereas its diffuse form, refers to calcinosis universalis, affects subcutaneous and fibrous structures of muscles and tendons. The pathophysiology of this condition is unknown and no effective therapy is currently available.3,4,5 Systemic lupus erythematosus can involve the myocardium, pericardium, cardiac valves,and coronary arteries. Myocarditis in SLE is not likely to produce major regional wall motion abnormalities but may contribute to global left ventricular dysfunction.7,8We report a young woman with SLE who developed calcinosis and myocarditis.